2020
DOI: 10.1080/14756366.2020.1758689
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 5-methyl-N-(2-arylquinazolin-7-yl)isoxazole-4-carboxamide analogues as highly selective FLT3 inhibitors

Abstract: A series of 4-arylamido 5-methylisoxazole derivatives with quinazoline core was designed and synthesised based on conformational rigidification of a previous type II FMS inhibitor. Most of quinazoline analogues displayed activity against FLT3 and FLT3-ITD. Compound 7d, 5-methyl-N-(2-(3-(4-methylpiperazin-1-yl)-5-(trifluoromethyl)phenyl)quinazolin-7-yl)isoxazole-4-carboxamide, exhibited the most potent inhibitory activity against FLT3 (IC 50 ¼ 106 nM) with excellent selectivity profiles over 36 other protein ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…On the other hand, FMS kinase has a Thr663 residue in the same sequence at the active site. Therefore, compound 8r could not form a π-π interaction with Thr663, which explains its selective inhibition between FLT3 and FMS kinase 21 . The positively charged nitrogen of the ethyl piperazine ring forms a π-cation interaction with His809.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, FMS kinase has a Thr663 residue in the same sequence at the active site. Therefore, compound 8r could not form a π-π interaction with Thr663, which explains its selective inhibition between FLT3 and FMS kinase 21 . The positively charged nitrogen of the ethyl piperazine ring forms a π-cation interaction with His809.…”
Section: Resultsmentioning
confidence: 99%
“…We found that core structures including benzimidazole and quinazoline play a key role in retaining their binding mode that interacts with the Phe691 residue in FLT3 kinase via π-π interaction by means of investigating molecular docking. On the process of structure optimisation to enhance activity, it was verified that indazole fragment could be employed as a hinge binder that binds with the ATP-binding pocket 21 ( Figure 3 ). Based on this observation, we replaced the isoxazole structure with various phenyl amide groups retaining its quinazoline core structure first and synthesised several derivatives, including 5-methylisoxazole-4-carboxamide and 3–(4-methylpiperazin-1-yl)-5-(trifluoromethyl)benzamide, which were considered as starting points to develop novel FLT3 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation